The pattern of public expenditure in Northern Ireland and the Republic 1954-65 - O'Loghlen, B. (Statistical and Social Inquiry Society of Ireland, 1968)
This paper attempts to compare the patterns of public expenditure, in Northern Ireland and the Republic, emphasising especially development expenditures. Although all public expenditures contribute to economic development, at least in the long-run, the paper concentrates on the investment spending of the public authorities in the two areas.
Read before the Society, 19 April 1968
Keywords: Public expenditure patterns, Northern Ireland; Public expenditure patterns, Ireland; Composition of public expenditure; 314.15